La mayor erupción pliniana del volcán Arenal, Costa Rica - Chiesa, Sergio (2013)
Among the pyroclastic products extruded by the Arenal volcano, one of the units is clearly distinctive in terms of particle size, thickness, areal extension and distance from the vent. This unit is the result of an explosive eruption of plinian type. From tephra analysis, the volume of the dacitic pyroclastics was determined as 0.4 km3, equivalent to 0.21 km3 of dense rock. The area covered was 1000 ± 100 km2 with a thickness ranging from 2-3 m to 5 cm. Archeological studies indicate that the eruption had place by 1000 ± 200 A.D..A comparison of this eruption with one of the pelean type dating from 1968, shows that the volume of the described plinian eruption was 6 times greater. The area covered has larger extension by a factor of 25. Another comparative analysis can be related to the plinian explosion of Mount St. Helens (U.S.A.) on May 18, 1980 where the area delimited by the 20 om isopach contour was 27 times smaller than the of "Unit 20" produced by the Arenal plinian eruption.